Tracked Changes. Radio-frequency connectors. RF coaxial connectors with inner diameter of outer conductor 16 mm (0, 63 in) with screw lock. Characteristic impedance 50 Ω (type 7-16) Part 4, (7th March 2023) - British Standards Institution,
No abstract available